Combined Dietary Anthocyanins, Flavonols, and Stilbenoids Alleviate Inflammatory Bowel Disease Symptoms in Mice - Scarano, Aurelia; Butelli, Eugenio; De Santis, Stefania; Cavalcanti, Elisabetta; Hill, Lionel; De Angelis, Maria; Giovinazzo, Giovanna; Chieppa, Marcello; Martin, Cathie; Santino, Angelo (Frontiers in Nutrition, 2018)
Dietary polyphenols are associated with a wide range of health benefits, protecting against chronic diseases and promoting healthy aging. Dietary polyphenols offer a complementary approach to the treatment of inflammatory bowel diseases (IBDs), a group of common chronic intestinal inflammation syndromes for which there is no cure. Tomato is widely consumed but its content of polyphenols is low. We developed a tomato variety, Bronze, enriched in three distinct classes of polyphenols: flavonols, anthocyanins, and stilbenoids. Using Bronze tomatoes as a dietary supplement as well as Indigo (high anthocyanins and flavonols), ResTom (high stilbenoids) and wild-type tomatoes, we examined the effects of the different polyphenols on the host gut microbiota, inflammatory responses, and the symptoms of chronic IBD, in a mouse model. Bronze tomatoes significantly impacted the symptoms of IBD. A similar result was observed using diets supplemented with red grape skin containing flavonols, anthocyanins, and stilbenoids, suggesting that effective protection is provided by different classes of polyphenols acting synergistically.